2003
DOI: 10.1111/j.1741-3737.2003.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Decline in Women's Household Labor: Individual Change and Cohort Differences

Abstract: individual and cohort change in housework are examined over a 13-year period. Responsibility for household tasks declined 10% from 1974-75 to 1987-88. For individual women, changes in housework are associated with life course shifts in time availability as well as with changes in gender attitudes and marital status, but are not related to changes in relative earnings. Cohort differences exist in responsibility for housework in the mid-1970s and they persist over the 13-year period. Overall, these findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 46 publications
4
94
2
5
Order By: Relevance
“…Studies show that women's and men's attitudes toward gender roles are consistent predictors of housework sharing (Artis & Pavalko, 2003;Blaisure & Allen, 1995;Brayfield, 1992;Greenstein, 1996;Lye & Biblarz, 1993;Potuchek, 1992;Shelton & John, 1993a;Thompson & Walker, 1989). Married men who have more egalitarian attitudes in early adulthood are also likely to participate more in routine housework later in life (Cunningham, 2005).…”
Section: Attitudes Toward Gender Rolesmentioning
confidence: 95%
“…Studies show that women's and men's attitudes toward gender roles are consistent predictors of housework sharing (Artis & Pavalko, 2003;Blaisure & Allen, 1995;Brayfield, 1992;Greenstein, 1996;Lye & Biblarz, 1993;Potuchek, 1992;Shelton & John, 1993a;Thompson & Walker, 1989). Married men who have more egalitarian attitudes in early adulthood are also likely to participate more in routine housework later in life (Cunningham, 2005).…”
Section: Attitudes Toward Gender Rolesmentioning
confidence: 95%
“…Artis & Pavalko (2003) found that despite growing numbers of households with dual earners and the common practice of pooling income to support a chosen lifestyle, women are still more likely to do the majority of housekeeping tasks, including being the primary carer of any children.…”
Section: Owning the Choice To Be Childlessmentioning
confidence: 99%
“…Ces idéologies peuvent être traditionnelles ou égalitaires (Taylor et al, 2015 : 14-15). Plusieurs recherches tendent à démontrer que l'idéologie genrée contribue à façonner la division du travail domestique (Artis et Pavalko, 2003 ;Cunningham, 2007). Une étude à grande échelle menée aux États-Unis (Brines, 1994) montre par exemple que les hommes traditionnels se trouvant dans une situation de dépendance économique par rapport à leur conjointe ont tendance à réparer cette transgression des rôles de genre en s'engageant moins dans les tâches domestiques.…”
Section: Enfances Familles Générations 26 | 2017unclassified